Formulation, Development and Characterization of Herbal Cream - Divya Devi,; Ashish Mishra,; Shilpi Mishra, (Asian Journal of Pharmaceutical Research and Development, 2025)
The greater part of the world's population relies on traditional medicine for their health care. This is also the case in the treatment of wounds. In developing countries, formulations prepared from plants have been widely used for the treatment of soft tissue wounds and burns by medical personnel trained in western medicine as well as by traditional practitioners. Skin nourishment is essential for maintaining healthy and radiant skin. With increasing awareness of the adverse effects of synthetic chemicals in cosmetic products, there has been a growing interest in natural alternatives. The objective of proposed work is to develop formulation and characterization of natural herbal cream containing aloe vera, Turmeric and masoor dal extract. The current research focuses on the formulation of a skin nourishing cream using Aloe vera, turmeric and masoor dal. Herbal cream containing Aloe barbadensis and Curcuma longa extracts and Red lentil (Massor dal) were formulated and evaluated for various parameters. From the results, obtained from the physical parameters such as spreadability, pH, viscosity and spreadability it was indicated that formulation ACHC2 was ideal and it was chosen for further characterization such as antimicrobial activity testing. The formulated polyherbal cream (ACHC2) was observed for its skin irritation study. From the result it was observed that it showed no skin irritation in animals.